Utilization of Used Cooking Oil in Pamijahan Village Through the JELITA Program (Used Cooking Oil as Liquid Plant Fertilizer) - Sarfat, Muhammad Syukur; Aryasatya, Dzaky; Kafy, Ahdan; Alya, Zahra; Wira, Nabila; Aisha, Pruwita; Eltanti, Widya; Reksa, Mugia; Vikram, Dio; Iqbal, Muhammad (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2026)
The Environmental Home Group (Kelompok Rumah Lingkungan – KRL) in collaboration with the Women Farmers Group (Kelompok Wanita Tani – KWT) revealed that one of the problems that they want to overcome in Pamijahan Village, Bogor Regency is how to utilize used cooking oil sourced from the Pamijahan Village community, especially in supporting agricultural activities currently being carried out by KWT. ​​This was also expressed by the Head of Pamijahan Village. Therefore, the JELITA Program (Used Cooking Oil as Liquid Plant Fertilizer) is present as a solution by processing used cooking oil into organic liquid fertilizer that is useful for the agricultural sector while reducing the impact of pollution. This program was implemented by 9 IPB University students and involved 20 people from Pamijahan Village, Bogor Regency. The liquid fertilizer production process includes collecting used cooking oil, mixing it with additional materials such as molasses, EM-4, and rice bran, and fermentation for 20 days. The results of this activity show that converting used cooking oil into liquid fertilizer can be an alternative approach in managing household waste. In addition, this program contributes to meeting local fertilizer needs so that it can reduce the use of conventional chemical fertilizers.